Long-term preservation solution for complex digital objects preserved as archival information packages in the domain of pharmaceutical records - Stančić, Hrvoje (Array, 2011)
The authors base their research on several standards: Reference Model for an Open Archival Information System (OAIS) ISO 14721 and Information and documentation - Records management processes - Metadata for records standard ISO 2381. They build a model for the long-term preservation of pharmaceutical records in the eCTD file format (electronic Common Technical Document - standard format for pharmaceutical documentation) stored in a digital archive. The model shows formation of archival information packages (AIPs) as structured, complex objects - based on eCTD's XML elements, packaged together with the appropriate metadata in a single object and protected for the preservation reasons by an integrated checksum creating MDx algorithm. An application based upon the developed model, upon initial mapping of eCTD's structure categories and metadata to the AIP's structure, is shown to be able to automate this process as much as possible. This procedure should enable users to use the application even for different types of complex digital objects, not only for eCTD. In that sense the application could become a generic 'preservation application' for the AIP creation and long-term preservation. The authors conclude that the developed model, exemplified by the eCTD documentation format and appurtenant application, could improve the AIP creation of pharmaceutical records intended for the long-term preservation in digital archives.